High-Frequency Repetitive Transcranial Magnetic Stimulation Could Improve Impaired Working Memory Induced by Sleep Deprivation. (12th December 2019) - Guo, Zhiwei; Jiang, Zhijun; Jiang, Binghu; McClure, Morgan A.; Mu, Qiwen
Abstract : Objective . To investigate whether and how the working memory impairment induced by sleep deprivation (SD) could be recovered by using repetitive transcranial magnetic stimulation (rTMS), as well as to clarify the corresponding brain activity changes. Methods . Seventeen healthy adults received one session of 5.0 Hz rTMS over the left dorsolateral prefrontal cortex (DLPFC) following 24 hours of SD. Resting state functional magnetic resonance imaging (fMRI) and working memory test were performed during a rested waking period, after SD and rTMS. The amplitude of low-frequency fluctuations (ALFF) was used to detect the spontaneous neural activity changes after both SD and rTMS. The relationship between ALFF and the performance of working memory was also assessed by using correlation analysis. Results . After SD, the participants exhibited lower response accuracies and longer reaction times on the working memory tests of letters and numbers. The decreased response accuracy of numbers was significantly improved after rTMS similarly to the state of the rested waking period after a normal night of sleep. ALFF values decreased from the rested waking period state to the state of SD in the brain regions involving the frontal gyrus, precuneus, angular gyrus, and parietal lobe which showed significantly increased ALFF after rTMS. Furthermore, significantly positive correlations were observed between changes of response accuracy and the changes of ALFF value of the inferior frontal gyrus and supramarginal gyrus. Conclusion . These results indicate that high-frequency rTMS applied over left DLPFC may contribute to the recovery of the impaired working memory after SD by modulating the neural activity of related brain regions.